2014
DOI: 10.1063/1.4880798
|View full text |Cite
|
Sign up to set email alerts
|

Extreme optical activity and circular dichroism of chiral metal hole arrays

Abstract: We report extremely strong optical activity and circular dichroism exhibited by subwavelength arrays of fourstart-screw holes fabricated with one-pass focused ion beam milling of freely suspended silver films. Having the fourth order rotational symmetry, the structures exhibit the polarization rotation up to 90 degrees and peaks of full circular dichroism and operate as circular polarizers within certain ranges of wavelengths in the visible. We discuss the observations on the basis of general principles (symme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 21 publications
6
39
0
Order By: Relevance
“…Moreover, chiroptical responses were studied in simple 1D metal grooves [33] and nanohole arrays [34]. Most of the chiral nanostructure fabrication involves sophisticated, challenging and expensive techniques; however, authors in [35][36][37] showed that complex chiral shapes can be produced in silver films by a conventional single-pass focused ion beam technique.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chiroptical responses were studied in simple 1D metal grooves [33] and nanohole arrays [34]. Most of the chiral nanostructure fabrication involves sophisticated, challenging and expensive techniques; however, authors in [35][36][37] showed that complex chiral shapes can be produced in silver films by a conventional single-pass focused ion beam technique.…”
Section: Introductionmentioning
confidence: 99%
“…Eq (15). versus wavelength, of a LCP wave incident on the square lattice of left twisted nanoholes(Fig.…”
mentioning
confidence: 98%
“…The absence of mirror symmetry being a common attribute of numerous natural objects and materials, especially those of biological origin, typically gives rise to very moderate optically observable consequences. Artificial chiral electromagnetic materials provide high and even sometimes extreme degrees of optical activity (OA) and circular dichroism (CD) 1 2 3 4 5 6 7 8 that may also appear via spontaneous symmetry breaking 9 and can possess additional functional properties such as strong nonlinearity 10 and tunability by irradiation 11 . Being unattainable with natural materials, these features are highly advantageous for the potential applications that range from electromagnetic signal manipulation 12 to nanoscale chirality diagnostics 13 .…”
mentioning
confidence: 99%